A Novel Modulation Technique with Low PAPR for 5G-IoT Systems. (25th July 2022) - Sun, Junchao; Chen, Buyu; Huang, Ding; Wang, Baobing; Xiang, Tian; Kong, Dejin
Abstract : For existing orthogonal frequency division multiplexing (OFDM) in 5G internet of things (5G-IoT) systems, one of the critical problems is the high peak to average power ratio (PAPR), which seriously degrades the energy efficiency. To this end, we propose a novel modulation technique with low PAPR for IoT systems, which preserves the advantage of low implementation complexity and ability to fight against multipath channels. The key methodology is the employment of symbol repetition in the frequency domain. Hence, by designing the appropriate phase factors on the repeated symbols, the PAPR of transmitted signals is equivalent to that of an OFDM signal with a reduced size of discrete Fourier transform (DFT). It is demonstrated that, even if there exists repetitive symbols, the proposed method can still maintain an unreduced spectral efficiency performance. Moreover, to evaluate the proposed method, the Monte-Carlo simulations are conducted for the complementary cumulative distribution function (CCDF) and the bit error rate under multipath fading channels. The simulations show that, as CCDF = 10 − 3, the proposed method can achieve 2.5 dB gains about the PAPR compared with the original OFDM signal.